(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
The objective of the research is the evaluation of quality parameters in laying foods in the Jiménez Municipality, Lara state, the estimation of the quality parameters was carried out using the standards and techniques for measuring the parameters of humidity, granulometry and densities, loose and compact and subsequent evaluation thereof, obtaining the results, in Posture 1,2,3 and 4, are: maximum humidity 11.5%m/m, minimum 9.3%m/m. In the case of density we have a maximum value (DC) 0.820g/mL and a minimum value of (DC) 0.676g/mL, in (DS) a maximum value 0.704g/mL and a minimum value of 0.14g/mL. In granulometry, a maximum value of the 4mm sieve is 16.01%m/m and a minimum of 15.17%m/m and in the 3.2.1mm and 600µ sieves we have a maximum value of 65.81%m /m and a minimum of 64.35%m/m. Among the improved formulations we have a maximum humidity of 11.5%m/m and a minimum of 9.2%m/m with a maximum (DC) of 0.85g/,L and a minimum (DC) of 0.69g. /mL with respect to the (DS) gives us a maximum value of 0.676g/mL and a minimum of 0.588g/mL, now later in the case of granulometry we have as results in this graph of improved formulation with a 4mm sieve we have as a maximum value of 15.3%m/m and a minimum of 12.05%m/m with respect to the 3.2.1mm and 600µ sieves yield the maximum value of 67.6%m/m and a minimum value of 63 .93%m/m.